Proliferating trichilemmal tumour: a case report with review of literature - Lakshmi, A. Bhagya; Rao, N. Subba; Das, Basumitra; Kartheek, B. V. S. (International Journal of Research in Medical Sciences, 2017)
Proliferating trichilemmal tumour is a solid-cystic neoplasm that shows trichilemmal differentiation similar to that of the isthmus of the hair follicle histologically characteristed by the presence of trichilemmal keratinization. Proliferating Trichilemmal Tumour (PTT) appears mainly in elderly women and is in general a solitary lesion on the scalp. Proliferating trichilemmal tumours generally have a benign clinical course, and a clinical differentiation from squamous cell carcinoma is often difficult. We report a case of PTT in a 30 year old man presenting as a solitary 10x8 cm ulcerated nodule on the scalp since 3 months clinically resembled a malignant tumour. The therapeutic approach is surgical removal with a wide clear margin.